2014
DOI: 10.1016/j.beem.2014.07.004
|View full text |Cite|
|
Sign up to set email alerts
|

Pharmacogenetics of osteoporosis

Abstract: Osteoporosis is a complex bone disorder with a strong genetic basis. The genetics of osteoporosis encompasses two main areas: genetics of disease susceptibility and pharmacogenetics of drug response. The former has been widely studied in the past few decades, while the latter is still largely untouched. This review will provide an overview of the pharmacogenetics of osteoporosis, focusing on the major recent advances in the past two years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 58 publications
0
8
0
2
Order By: Relevance
“…In any case, all the mechanisms may also be the cause of different impacts of individual polymorphisms on the analysed parameters. Other limitations can involve gene-gene and gene-environment interactions, or epigenetic factors which could influence the pharmacodynamics and pharmacokinetics of individual drug response [ 18 ]. Nevertheless, the pharmacogenetic research is promising, especially for osteoporosis, that require long-term treatments and where different therapy types exist to be alternatively chosen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In any case, all the mechanisms may also be the cause of different impacts of individual polymorphisms on the analysed parameters. Other limitations can involve gene-gene and gene-environment interactions, or epigenetic factors which could influence the pharmacodynamics and pharmacokinetics of individual drug response [ 18 ]. Nevertheless, the pharmacogenetic research is promising, especially for osteoporosis, that require long-term treatments and where different therapy types exist to be alternatively chosen.…”
Section: Discussionmentioning
confidence: 99%
“…SERMs are used for prevention and treatment of postmenopausal osteoporosis and breast cancer prevention in high-risk postmenopausal women with osteoporosis [ 17 ]. Raloxifene, a member of SERMs, simulates estrogen action on the skeletal system through agonistic binding to estrogen receptors without the negative effects on breast and endometrium [ 18 ]. As in the case of association studies, the results of pharmacogenetic ones have not always been consistent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note, however, that most data on post-menopausal women available in the literature has been obtained from Caucasian populations aged 65 or over, and that information from other ethnic groups is limited. 39 Finally, we considered whether unmeasured confounders may have introduced spurious associations between BMD and incident fracture. Indeed, the assumption of sequential ignorability was probably not met in this study because BMD slopes were observed after participants were randomly allocated to placebo and BZA groups.…”
Section: Discussionmentioning
confidence: 99%
“…By binding to calcitonin receptors in bone and the brain, osteoclastic activity is diminished and analgesic effects are mediated. Salmon calcitonin is currently marketed and has been shown to be significantly more potent than human calcitonin [24, 25]. Gastrointestinal symptoms have been observed, but these effects can be minimized with different modes of administration.…”
Section: Osteoporosis Treatmentsmentioning
confidence: 99%